Post Dural Puncture Headache After Elective Caesarean Section Using 27 G Quincke and Whitacre Spinal Needles: A Comparative Study - Baral, Pawan Puspa; Pathak, Laxmi; Udaya, Rejin Kumar; Lawoju, Anita; Pokhrel, Sita; Gupta, Pramod Kumar (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION Post-dural puncture headache (PDPH), a serious complication of spinal anesthesia (SA) may persevere for long time and can be unbearable to the patients. The incidence of PDPH unswervingly relies on the size of the spinal needles used and this gradually decreases with the use of thinner spinal needles. MATERIAL AND METHODS A prospective randomized single blinded study was conducted during the period between 1 to 29 January 2019, at Universal College of Medical Sciences, Nepal. A total of 120 patients (between 20-35 years of age) were divided into two groups: Group I: 60 patients given SA with 27-G Quincke needle and Group II: 60 patients given SA with 27-G Whitacre. Randomization was done by coin tossing method and double-blinded except for the anesthetist performing the spinal block. Patients were interviewed on days 1 to 5 and were questioned with regard to headache based on its severity, location, character, duration, associated symptoms (nausea, vomiting, auditory and ocular symptoms). The severity of the headache was analyzed by Crocker scale. RESULTS The results showed that 33% more headache in group A, but the t-value was 0.727 and p-value was 0.2345 which was statistically insignificant. CONCLUSION Hence, using 27-G Quincke spinal needles does appear to be advantageous to the patients whereas, Whitacre spinal needles are shown to be clearly associated with fewer cases of PDPH.